POSISI PEREMPUAN DALAM GERAKAN POLITIK (Tinjauan HAM dan PERDA Syari’ah) - Zakiah, Sitti (LPPM IAIN Parepare, 2017)
This article describes briefly about the political movements of Islamic civil society organizations as well as influencing the position of women in their political movements. Since Indonesia has not been independent, the emergence of community organizations (mass organizations) Islam gives the color of socio-political life, including law. It is not surprising that a number of regional heads include Islamic law in local regulations. With full support, religious figures, MUI, Islamic mass organizations and legislatures of a number of sharia laws are passed. Euforia PERDA syariah gained the right momentum since Law no. 31 of 2004 on Regional Government; and Law No. 33 of 2004 on Fiscal Balance between the Central Government and Local Government is enacted. However, there are articles in Islamic law that are gender biased. There is a negative stigmatization of women. It is as if women are triggering immorality and evil. In a legal state, stigmatization is against human rights. Where the rights of justice and equality before the law are enforced in state regulations, including sharia law.